General Description of Self Esteem on New Students in Indonesia: Gambaran Umum Self Esteem Pada Mahasiswa Baru di Indonesia - Muhammad Indra Astrawan (CV. Cendekiawan Muda Sriwijaya, 2025)
The transition period into a new student is a very difficult time for humans with various challenges in self-adjustment, one of which is related to the level of self-esteem. Self-esteem plays an important role in shaping students' self-confidence and psychological resilience in facing a new environment. This study aims to determine the level of self-esteem of new students in Indonesia and compare self-esteem in male and female students. This study used a descriptive quantitative approach with a survey method of 41 new students from various universities and faculties in Indonesia with an age range between 17-19 years. The results showed that most students were in the moderate self-esteem category, with smaller numbers in the high and low categories. In addition, there are differences in self-esteem levels based on gender, where male students tend to have higher self-esteem than female students. This finding indicates the importance of paying attention to self-esteem development, especially in new female student groups. The implications of this study can be the basis for higher education institutions to design psychological or psychoeducational assistance programs that support the improvement of new students' self-esteem in order to support the academic abilities and social adjustment of female students in their environment.